1994
DOI: 10.2214/ajr.163.6.7992745
|View full text |Cite
|
Sign up to set email alerts
|

Vascular contact with the fifth cranial nerve at the pons in patients with trigeminal neuralgia: detection with 3D FISP imaging.

Abstract: OBJECTIVE.Vascular contact with the trigeminal nerve at the pens is known to cause trigeminal neuralgia; however, this finding also is present in some asymptomatic subjects. or absence of vascular contact with, or deformity of, the fifth cranial nerve in patients for whom surgery is planned for treatment of trigeminal neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 0 publications
3
37
2
1
Order By: Relevance
“…The introduction of the operating microscope led to increasing use of microvascular decompression as a treatment for TGN (Janetta, 1976). The ability to visualize and localize aberrant blood vessels by means of advances in radiographical techniques (Meaney et al, 1994) (Fig. 1) has led to a much more widespread and effective use of microvascular decompression (Barker et al, 1996).…”
Section: Surgicalmentioning
confidence: 99%
“…The introduction of the operating microscope led to increasing use of microvascular decompression as a treatment for TGN (Janetta, 1976). The ability to visualize and localize aberrant blood vessels by means of advances in radiographical techniques (Meaney et al, 1994) (Fig. 1) has led to a much more widespread and effective use of microvascular decompression (Barker et al, 1996).…”
Section: Surgicalmentioning
confidence: 99%
“…In a prospective study of patients with TGN and age-and sex-matched controls, high-resolution MRTA identified vascular compression in 85% of symptomatic patients compared to 8% in the controls, and in a study comparing surgical findings with MRTA, sensitivity and specificity were high [3]. In such patients, excellent results are obtained from MVD.…”
Section: Discussionmentioning
confidence: 98%
“…Diagnostic MR and MRTA scans were performed using a Siemens Magnetom 1.5-tesla MR scanner using the sequence described in which arterial blood flowing into the block gives a high signal; separate acquisitions were performed with and without gadolinium, the addition of which makes veins visible and often makes the arteries more obvious [3,4]. The Surgical Technique MVD was performed as described [2].…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Anterior inferior cerebellar artery, posterior inferior cerebellar atery or the vertebral artery form a loop under, over or between the VII and VIII cranial nerves and may produce symptoms, if the compression coincides with the glial Schwann cell junction. New strict criteria have been developed for the diagnosis of neurovascular conflict that in appropriate clinical setting, the vessel should be an artery, site of contact must be the root entry zone with the vessel crossing the nerve perpendicularly, and the nerve must be deviated or indented by the offending vessel or compressed or encased between two or more vessels.…”
Section: Vascular Lesionsmentioning
confidence: 99%